2014
DOI: 10.1016/j.tdj.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the antiapoptotic survivin in the adenomatoid odontogenic tumors

Abstract: Background: Adenomatoid odontogenic tumor (AOT) is an uncommon benign epithelial odontogenic tumor. Expert morphological diagnosis is required to establish differential diagnosis, in particular from ameloblastoma, thus preventing extensive surgery. Objective: To clarify the histopathological features of AOT, as well as to assess the immunohistochemical expression of survivin in AOT. Material and methods: Ten specimens of AOT, and one specimen of tooth germ as a control were collected from the archival files of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…ElSheikh et al . [ 9 ] who used an immunohistochemical technique to examine the expression of survivin in AOT specimens and tooth germ specimens as a control. The reaction was mostly found in duct-like structures and whorled pattern spindle cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ElSheikh et al . [ 9 ] who used an immunohistochemical technique to examine the expression of survivin in AOT specimens and tooth germ specimens as a control. The reaction was mostly found in duct-like structures and whorled pattern spindle cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] As per the majority of reports, Adenomatoid Odontogenic Tumor (AOT) frequently manifests as a slow-growing, painless mass affecting the anterior maxilla, with three clinical subtypes that all have the same histology: follicular type (73%), extra-follicular variant (24%), and peripheral (3%). [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these authors also demonstrated that while the lymph node involvement increased,thesurvivaldecreased,regardlessofthesize oftumor;and,onthecontrary,assizeoftumorincreased, the survival status decreased, regardless of thelymphnodeinvolvement.However,therelation between the size of tumor and the lymph nodes in breastcancerwasbeyondthescopeofourstudy.Instead,wewereinterestedintherelationbetweenthe lymphnodestatusandthesubcellularlocalizationof survivinand,asaresult,wedidnotconfirmanysignificantcorrelation. [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from tumours, the protein is highly expressed in embryonic and foetal tissues, but is completely absent in terminally differentiated adult cells (Chang et al, 2004;Lechler et al, 2007;Xue et al, 2012;Jaiswal et al, 2015). The survivin expression in embryonic and foetal development contributes to tissue homeostasis and differentiation (Adida et al, 1998;ElSheikh et al, 2014). Survivin expression is highly regulated by the cell cycle and the protein is only expressed in the G2-M phase (Altieri, 2008;Jaiswal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%